THE TEXTUAL TRADITION OF THE ETHIOPIC VITA OF SAINT MARK THE EVANGELIST: THE MEDIUM RECENSION IN FOCUS (Journal of Oriental Studies, 2026)
The Ethiopic Vita of Saint Mark the Evangelist represents a rich textual tradition that indicates the complex processes of translation, transmission, and adaptation within the Ethiopian Christian literature. This study aims to describe the textual history of the Gəʿəz Acts of Saint Mark the Evangelist whose life traces back to the 1st century CE. His Vita, on which this study is focused, is supposed to be composed in Greek and translated into Gəʿəz in the 4th century CE. The text written in Gəʿəz is preserved in seven extant manuscripts entitled, “Gädlä Marəqos”, which commonly deals with the combat and martyrdom of the Saint. Through analyzing key textual features and comparing different manuscript versions, the study explores how the Ethiopic tradition has shaped the historical narration of Saint Mark to reflect its textual tradition. Hence, collected from different Churches and Monasteries, the witnesses are said to be themain sources of the data used for this article. On the basis of the data collected from the manuscripts, the textual tradition of the text has been described in detail qualitatively. Besides, the sources of the text, the narrative structure and the text arrangement have been displayed in their respective order. Based on the text tradition, the hypothetical relations of the witnesses to their ancestor could be formulated as: Ω = α (A + γ (E1 + E2) + β (δ (ε (B+ F) + C) +D). This article may help to have a wide range of understanding towards the Ethiopian engagement in the early Christian traditions along with the role of translation in preserving and transforming hagiographical texts.Keywords: textual transmission, Mark the Evangelist, conjunctive error, stemma codicum, manuscript tradition.